Applications of sensory marketing strategies to increase customer retention in the Turkish airline industry through customer experience - Aydemir, İsmail (İstanbul Bilgi Üniversitesi, 2019)
The primary aim of this research is analyzing the relationship between sensory marketing strategies and customer retention in the airline industry. Also, this research will show us how customers perceive sensory marketing strategies of airlines companies. Since some service quality elements also include sensory implications, service quality evaluation is also included to this study. In order to understand customers’ perceptions and insights, an online survey is designed. The survey consists of 4 parts that include questions about demographic information of respondents, flying habits, company evaluation and flight experience. A quantitative research method is applied to analyze the survey results. Aviation industry is a very broad term for that reason, the subject is narrowed to sensory marketing implementations in the industry. In this study, research questions and hypothesis are shaped according to the depth of the subject. The industry itself has many brands that are directly competing with each other and each brand has unique marketing strategies. In this study, how those strategies are affecting customer’s purchasing behavior is examined.

Bu tezin ana amacı hava yolu firmalarının uygulamış olduğu duyusal pazarlama stratejileri ile tüketici kazanımı arasındaki ilişkiyi incelemektir. Ayrıca bu çalışma hava yolu firmalarının uygulamış oldukları stratejilerin tüketiciler tarafından nasıl algılandığını da gösterecektir. Hizmet kalitesi faktörleri de duyusal pazarlama uygulamaları içerdiğinden, havayolu firmalarının hizmet kalitesinin değerlendirilmesi de çalışmaya dâhil edilmiştir. Tüketicilerin algısını ve izlenimlerini anlamak için çevrimiçi anket hazırlanmıştır. Anket dört bölümden oluşmakta olup; demografik bilgiler, uçuş alışkanlıkları, marka değerlendirmesi ve uçuş deneyimleri hakkında sorular içermektedir. Anket sonuçlarını analiz etmek için kantitatif metot kullanılmıştır. Hava yolu endüstrisi çok geniş bir tanımlama olup, incelenmesi kolay olmayacaktır. Bu yüzden araştırma soruları ve oluşturulan hipotezler konunun daraltılmasına ve konunun şekillenmesine yardımcı olacaktır. Sektör birbiri ile direk rekabet içinde olan birçok firmadan oluşmaktadır ve her bir firmanın kendine özgü pazarlama stratejileri bulunmaktadır. Bu çalışmada, bu stratejilerin tüketicilerin satın alma davranışlarını nasıl etkilediği test edilecektir.
Türkiye'de hizmet veren havayolu firmalarının müşteri tutundurmasını arttırmak için tüketici deneyimi sırasında uyguladıkları duyusal pazarlama stratejileri